Proceedings of the 2nd International Conference on Sports Sciences and Health 2018 (2nd ICSSH 2018) 2019
DOI: 10.2991/icssh-18.2019.42
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive Breastfeeding Survival And Factors Related to Early Breastfeeding Cessation in Indonesia

Abstract: Give only breast milk for the first six months is recommended for optimizing the infant's growth and development. In fact, the rate of exclusive breastfeeding in Indonesia is relatively low. This study was aimed to assess the survival probability of exclusive breastfeeding and identify the factors related to early breastfeeding cessation. This study used cross sectional design with sample of 1088 mothers of infants aged 6-12 months. Data were obtained from The Indonesian Family Life Survey (IFLS) wave 5 that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The median time for cessation of EBF was similar to a study done in northeastern Ethiopia, 12 southern Ethiopia, 31 and northern Ethiopia. 32 In this, the median time to cease EBF was higher than studies revealed from Indonesia, 33 Australia, 34 Kinshasa, 35 Botswana, 36 Colombia, 37 and Saudi. 38 The rate of early EBF discontinuation was 45.8%, which was higher than the studies revealed from southern Ethiopia 30.4%, 39 northwest Ethiopia 21.5%, 40 northeastern pastoralist parts of Ethiopia 35.5%, 12 Addis Ababa 42.4%, 41 mini Ethiopian demographic health survey 41%, 10 Taiwan 40.1%, 42 Kinshasa 2.8%, 35 India 22.85%, 43 Indonesia 21.3%, 33 and Kenya 2%.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The median time for cessation of EBF was similar to a study done in northeastern Ethiopia, 12 southern Ethiopia, 31 and northern Ethiopia. 32 In this, the median time to cease EBF was higher than studies revealed from Indonesia, 33 Australia, 34 Kinshasa, 35 Botswana, 36 Colombia, 37 and Saudi. 38 The rate of early EBF discontinuation was 45.8%, which was higher than the studies revealed from southern Ethiopia 30.4%, 39 northwest Ethiopia 21.5%, 40 northeastern pastoralist parts of Ethiopia 35.5%, 12 Addis Ababa 42.4%, 41 mini Ethiopian demographic health survey 41%, 10 Taiwan 40.1%, 42 Kinshasa 2.8%, 35 India 22.85%, 43 Indonesia 21.3%, 33 and Kenya 2%.…”
Section: Discussionmentioning
confidence: 52%
“…32 In this, the median time to cease EBF was higher than studies revealed from Indonesia, 33 Australia, 34 Kinshasa, 35 Botswana, 36 Colombia, 37 and Saudi. 38 The rate of early EBF discontinuation was 45.8%, which was higher than the studies revealed from southern Ethiopia 30.4%, 39 northwest Ethiopia 21.5%, 40 northeastern pastoralist parts of Ethiopia 35.5%, 12 Addis Ababa 42.4%, 41 mini Ethiopian demographic health survey 41%, 10 Taiwan 40.1%, 42 Kinshasa 2.8%, 35 India 22.85%, 43 Indonesia 21.3%, 33 and Kenya 2%. 44 This finding was lower than the study revealed from southern Ethiopia 48%, 45 Dukem Central Ethiopia 75.7%, 46 Nepal 50.5%, 47 Tanzania 68.7%, 48 Saudi 60%, 49 and Australia 49%.…”
Section: Discussionmentioning
confidence: 52%
“…Various factors may influence the mother’s inability to give exclusive breastfeeding, such as education, work and other support [ 22 ]. Other studies has also found that a low education level of the mother affects the success of exclusive breastfeeding due to many misconceptions [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%